(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
In this study, attempts were made to design and developed disintegrating drug delivery system; Acetaminophen fast disintegrating tablet (AFDT) by combining superdisintegrants and direct compression method. Acetaminophen is widely used as â€œover the counter (OTC)â€ and â€œcommon household drugâ€ as analgesic and antipyretic along with poor absorption due to first pass metabolism. So, we aimed to use our novel delivery system to achieve rapid absorption in patients like mentally ill, bed ridden and those who do not have easy access to water. The AFDT were produced by combining three superdisintegrants like croscarmellose, crospovidone and sodium starch glycolate in 4% w/w as ratio of (1:1, 1:2, 2:1) using direct compression method. The optimized batch (A3) of tablet were evaluated for postcompression parameters like hardness (4.5 Â± 0.75 kg/cm2), friability (0.76%), wetting time (42 Â± 0.92 s), water absorption ratio (98.6%), disintegration time (24.00 Â± 0.83 s) were found to be acceptable according to standard limits. The in vitro release rate of acetaminophen from AFDT was found to be more than that simple formulation in pH (5.8) using United State Pharmacopoeia dissolution test apparatus Type II. These results indicated that, the new AFDT formulation system combined advantage of faster release of acetaminophen, which had better effects of rapid oral absorption. Therefore, the AFDT may be used as fast disintegrating delivery system for OTC drug with poor absorption due to first pass metabolism.